PENGARUH METODE POGIL (PROCESS ORIENTED GUIDED INQUIRY LEARNING) TERHADAP KETERAMPILAN PROSES SAINS SISWA PADA MATERI SUHU DAN KALOR KELAS X SMA - Puji Eka Ningsih; Siswoyo Siswoyo; I Made Astra (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This study aims to determine the effect of applying the method POGIL ( Process Oriented Guided Inquiry Learning ) against the science process skills of high school students of class X on material Temperature and Heat . This research was conducted in SMA 102 Jakarta in April-May 2015. Samples were obtained by purposive random sampling technique which consists of two classes , namely X IIS 3 as an experimental class and X IIS 4 as the control class , each class consists of 34 students. Method in this study is quasi-experimental. Design research is pretest - posttest control group design, and the instrument used was a multiple choice test booklet reasoned as supporting data. The hypothesis for this study is there are significant POGIL method to science process skills of students in learning physics class X subject of temperature and heat.Keywords : POGIL, Science Process Skills.